Examining Physician Counselling to Promote the Adoption of Physical Activity - Spink, Kevin S. (Can J Public Health, 2008)
BACKGROUND: While the benefits of physical activity are generally recognized, over half of adult Canadians are not active enough to receive those benefits. Physicians may influence patient activity through counselling; however, research is inconsistent regarding their effectiveness in doing so. Increasing patients’ use of self-regulatory skills in managing their activity and additional telephone support are suggested as two means of improving physician counselling. When assessing the effectiveness of physician counselling, it may be important to measure both outcome and treatment adherence. We compared physician-directed activity counselling (modified PACE protocol) with a modified PACE protocol augmented with telephone-based counselling for patient support for both outcome and treatment adherence. METHODS: Physicians counselled 90 patients using a modified PACE protocol that included self-regulatory skills. Physical activity was assessed by questionnaire at baseline (prior to counselling) and one month later. Participants were divided into two groups: counselling (modified PACE counselling) and enhanced counselling (modified PACE counselling plus telephone support). RESULTS: The main outcome (mean energy expenditure) and secondary outcomes of treatment adherence (frequency, frequency of moderate activity, and duration) significantly increased over time (p<0.05). No significant interactions between group and time were found. INTERPRETATION: Our results support the effectiveness of physician counselling for activity that included the use of self-regulation skills. The effectiveness of telephone support over and above that of physician counselling was not supported. Our results demonstrate that assessing treatment adherence provides a means of discerning whether the counselling intervention was delivered as intended.